Can processes make relationships work? The Triple Helix between structure and action. (1st December 2014) - Grant, Kevin; , Martin Meyer; Kuusisto, Jari
Abstract : This contribution seeks to explore how complex adaptive theory can be applied at the conceptual level to unpack Triple Helix models. We use two cases to examine this issue – the Finnish Strategic Centres for Science, Technology & Innovation (SHOKs) and the Canadian Business-led Networks of Centres of Excellence (BL-NCE). Both types of centres are organisational structures that aspire to be business-led, with a considerable portion of their activities driven by (industrial) users' interests and requirements. Reflecting on the centres' activities along three dimensions – knowledge generation, consensus building and innovation – we contend that conceptualising the Triple Helix from a process perspective will improve the dialogue between stakeholders and shareholders.